PENGARUH METODE SCRAMBLE TERHADAP HASIL BELAJAR IPA SISWA KELAS IV DI GUGUS IV KECAMATAN MATARAM TAHUN PELAJARAN 2018/2019 - Intan Dwi Sahara; Ratnadi Ratnadi; Muhamad Tahir; Mansur Hakim (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2022)
This research aimed to know if there is a significance effect using scramble method through students' learning achievement at grade IV IPA Cluster IV Subdistrict Mataram Academic Year 2018/2019. This research used experimental qualitative method a type of Quasi Experimental Design which Nonequivalent Control Group Design. The population of this research was all the students at grade forth in Cluster IV Subdistrict Mataram. Probability sampling was used to get the sample in this research which gain class IV in SDN 35 Mataram and SDN 44Mataram as the sample. The data collection technique in this research used learning implementation observation sheets and cognitive learning achievement test which is pre-test and post-test. Data from the observation of learning implementation using the Scramble method were analyzed by using descriptive analysis, which are teaching and learning process during the two meetings could reach 100% (very good). The result of cognitive learning achievement (pre-test and post-test) were analyzed by using covariance analysis, get the alpha score 0,029< 0,05 in experimental group and the score in the controlling group was 61,259 > 52,024 . It showed that Ho is rejected and H alternative is accepted which stated there is significance effect using Scramble as a method through students' learning achievement at grade IV IPA Cluster IV Subdistrict Mataram Academic Year 2018/2019. The use of Scramble method in learning process can affect the students' learning achievement, and it is being suggested to use it in teaching and learning process..